RECORDING AND PUBLISHING OF MARRIAGE BOOK IN ORDER TO PREVENT UNREGISTERED MARRIAGE IN BATANGKUIS DISTRICT - Sembiring, Idha Aprilyana; Chairi, Zulfi; Aflah (Talenta Publisher, 2018)
This community empowerment and development program aims to increase public awareness, especially marriage couples in Batangkuis District in legalizing their marriages. Basically, the couples have known the necessity of registering marriages, but do not register for various reasons. They do not have a marriage book even though they have been married for a long time.To achieve this goal, two (2) phases of activities were carried out, (1) Legal counseling carried out for two days in two partner villages with the theme of the introduction, usefulness and benefits of marriage registration and legal consequences arising from not registering marriages and to (2) assistance activities in making marriage books. The targets are couples in the two partner villages who have long been married religiously but have not registered marriage. After legal counseling about the benefits and importance of marriage registration, there was an enthusiasm to ask for assistance in recording their marriages because most of the couples had been married for a long time and had many children but had no evidence of legality of their marriage. The enthusiasm of the husband and wife shows the approach through legal counseling is effective to move their legal awareness to register their marriages.